Five new species of Miconia (Melastomataceae) from the Central Peruvian Andes - Cardenas, Lizeth A; Burke, Janelle M; Michelangeli, Fabian A (Phytotaxa, 2014)
We describe five new species of Miconia (Melastomataceae) from Yanachaga Chemillén National Park and vicinity in Pasco, Peru: Miconia cardenasiae, Miconia chemillensis, Miconia humifusa, Miconia odoratissima, and Miconia pozuzoana. These species occur across a range of ecological habitats in the central Andes of Peru. Two of these species exhibit modifications for plant-arthropod interactions as leaf domatia and one of them has hollow stems. The number of previously undescribed species presented here from a relatively small area underscores the continued need for alpha taxonomy in the tropical Andes. Based on restricted distribution and habitat degradation pressure, we recommend that all species be categorized as either Endangered or Critically Endangered under IUCN guidelines.